Sovereign Debt Standstills - Hatchondo, Juan Carlos (IMF Working Papers; Working Paper, 2020)
As a response to economic crises triggered by COVID-19, sovereign debt standstill proposals emphasize debt payment suspensions without haircuts on the face value of debt obligations. We quantify the effects of standstills using a standard default model. We find that a one-year standstill generates welfare gains for the sovereign equivalent to a permanent consumption increase of between 0.1% and 0.3%, depending on the initial shock. However, except when it avoids a default, the standstill also implies capital losses for creditors of between 9% and 27%, which is consistent with their reluctance to participate in these operations and indicates that this reluctance would persist even without a free-riding or holdout problem. Standstills also generate a form of 'debt overhang' and thus the opportunity for a 'voluntary debt exchange': complementing the standstill with haircuts could reduce creditors' losses and simultaneously increase welfare gains. Our results cast doubts on the emphasis on standstills without haircuts.